2011
DOI: 10.1186/1476-4598-10-82
|View full text |Cite
|
Sign up to set email alerts
|

The monoclonal antibody Zt/f2 targeting RON receptor tyrosine kinase as potential therapeutics against tumor growth-mediated by colon cancer cells

Abstract: BackgroundOverexpression of the RON receptor tyrosine kinase contributes to epithelial cell transformation, malignant progression, and acquired drug resistance. RON also has been considered as a potential target for therapeutic intervention. This study determines biochemical features and inhibitory activity of a mouse monoclonal antibody (mAb) Zt/f2 in experimental cancer therapy.ResultsZt/f2 is a mouse IgG2a mAb that is highly specific and sensitive to human RON and its oncogenic variants such as RON160 (ED50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 36 publications
(63 reference statements)
2
47
0
Order By: Relevance
“…Various studies have shown that therapeutic antibodies and TKIs specific to RON inhibit tumor growth mediated by pancreatic, colon, and breast cancer cells in mouse tumor xenograft models (7,12,13,31). Studies using BMS-777607 to target MET have shown the effectiveness in inhibiting MET-mediated tumor cell migration, matrix invasion, and distance metastasis (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that therapeutic antibodies and TKIs specific to RON inhibit tumor growth mediated by pancreatic, colon, and breast cancer cells in mouse tumor xenograft models (7,12,13,31). Studies using BMS-777607 to target MET have shown the effectiveness in inhibiting MET-mediated tumor cell migration, matrix invasion, and distance metastasis (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Further treatment with neutralizing mAbs in addition to down regulating RON-β chain expression also inhibits the expression of pro-RON. It was observed that treatment with Zt/f2 causes tumor regression in as early as five days of administration in xenograft mouse model [60]. An in vitro assay shows that although the antibody induces the phosphorylation of RON receptor initially it subsequently leads to receptor internalization and thus favourable biological outcomes.…”
Section: Ron Signaling In Crcmentioning
confidence: 99%
“…The prospect of clinically targeting RON is currently being explored by the two main strategies -the development of neutralizing monoclonal antibodies and use of small molecule kinase inhibitors. The monoclonal antibodies (mAb) used to study the effect of blocking RON signaling pathways in CRC include Zt/f2, Zt/g4, Zt/c9 and Zt/c1 and act by inducing receptor internalization followed by protein degradation [58][59][60]. Zt/g4 and Zt/c9 both recognize epitopes on the sema sequence while Zt/f2 binds with epitopes on the IPT domain.…”
Section: Therapeutic Targeting Of Ron Kinasementioning
confidence: 99%
“…These observations provide the rationale for targeting RON as a potential cancer therapy (13,14). At present, inhibition of RON by therapeutic monoclonal antibodies (mAb) and small-molecule inhibitors (SMI) has been studied in preclinical models (10,(15)(16)(17). Partial inhibition of tumor growth in animal xenograft models has been observed (10,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…At present, inhibition of RON by therapeutic monoclonal antibodies (mAb) and small-molecule inhibitors (SMI) has been studied in preclinical models (10,(15)(16)(17). Partial inhibition of tumor growth in animal xenograft models has been observed (10,(15)(16)(17). Further inhibition is achieved by RON-targeted mAb or SMI in combination with chemotherapeutic agents (15).…”
Section: Introductionmentioning
confidence: 99%